Presencia de las clases populares en la historia republicana - Rénique, José Luis (1978)
There is a kind of widespread and commonly accepted "official version" of our republican history. In it appear with different relevance characters, institutions and dates, true epics and numerous acts of undeniable dedication; however, there are few spaces through which it is possible to learn about the life of the town, an actor par excellence in history.